2015
DOI: 10.1017/brimp.2015.33
|View full text |Cite
|
Sign up to set email alerts
|

Facial Emotion Recognition and Faux Pas Interpretation in Multiple Sclerosis

Abstract: Multiple sclerosis (MS) is an inflammatory disease of the central nervous system leading to physical and cognitive disability. The impact of the disease on social cognition has only come to light quite recently. The aim of this study was to evaluate the social cognition abilities of MS patients and their links with characteristics of the disease, such as physical disability, cognitive impairment and disease duration. The performances of a group of 64 MS patients were compared with that of 30 matched healthy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
2
5
1
1
Order By: Relevance
“…In our study, patients also had difficulty recognizing the facial emotions of fear and sadness, and a statistical trend was observed for disgust recognition. In contrast to previous reports, no deficit was observed for anger recognition in the MS sample relative to controls (Henry et al, 2015, 2011, 2009; Krause et al, 2009; Lenne et al, 2014; Prochnow et al, 2011). These deficits cannot simply be explained by a facial recognition deficit, as patients with MS were only included in our study if their BFRT score was within the normal range.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In our study, patients also had difficulty recognizing the facial emotions of fear and sadness, and a statistical trend was observed for disgust recognition. In contrast to previous reports, no deficit was observed for anger recognition in the MS sample relative to controls (Henry et al, 2015, 2011, 2009; Krause et al, 2009; Lenne et al, 2014; Prochnow et al, 2011). These deficits cannot simply be explained by a facial recognition deficit, as patients with MS were only included in our study if their BFRT score was within the normal range.…”
Section: Discussioncontrasting
confidence: 99%
“…The present study was designed to (a) confirm ToM and facial emotion recognition deficits in MS, (b) explore ToM and facial emotion recognition in patients with three MS subtypes, and (c) examine the impact of clinical disease characteristics and cognitive deficits, in particular executive deficits, on these processes. Consistent with previous studies, patients with MS performed significantly worse than healthy controls on the measures of facial emotion recognition (Henry et al, 2009;Phillips et al, 2011;Prochnow et al, 2011) and ToM (Banati et al, 2010;Henry et al, 2015Henry et al, , 2011Ouellet et al, 2010;Roca et al, 2014). Patients scored lower than healthy participants for all three levels of ToM, suggesting that individuals with MS have a specific ToM impairment even for simple inferences such as first-order mental state attributions.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…An additional goal of the current study is to characterize the relationship between cognitive deficits and social cognitive deficits in MS, which is currently debated (Cotter et al, 2016). Although some studies have shown that social cognition in MS is significantly correlated with one's general cognition, and thus, social cognitive deficits may be explained by underlying impairments in processing speed or executive function (Ciampi et al, 2018;Henry et al, 2015Henry et al, , 2017, other studies have found cognition and social cognition to be dissociable in MS (Batista et al, 2018;Raimo et al, 2017). As there is still limited research in this area, a better understanding of the specific mechanisms contributing to social cognitive impairments in MS will allow for more refined treatments and interventions.…”
Section: Introductionmentioning
confidence: 99%